Isolation, cultivation and immunofluorescence characterization of lamellar keratinocytes from equine hoof by using explants - Pfeifer, João P.H. [UNESP]; Santos, Vitor H. [UNESP]; Rosa, Gustavo [UNESP]; Souza, Jaqueline B. [UNESP]; Watanabe, Marcos Jun [UNESP]; Fonseca-Alves, Carlos E. [UNESP]; Deffune, Elenice [UNESP]; Alves, Ana L.G. [UNESP] (FapUNIFESP (SciELO), 2019)
The importance of the hoof to the horse health is clear, and the current knowledge regarding the cellular aspects of hoof keratinocytes is poor. Studies on equine keratinocyte culture are scarce. Developing keratinocyte cultures in vitro is a condition for studies on molecular biology, cell growth and differentiation. Some methods have already been established, such as those for skin keratinocyte culture. However, few methodologies are found for lamellar keratinocytes. The objective of this study was to standardize the equine hoof keratinocyte isolation and cultivation, and then characterize the cell immunophenotype. For this, the primary culture method used was through explants obtained from three regions of the equine hoof (medial dorsal, dorsal, and lateral dorsal). After the cell isolation and cultivation, the cell culture and its explants were stained with anti-pan cytokeratin (pan-CK) (AE1/AE3), vimentin (V9), p63 (4A4), and Ki-67 (MIB-1) antibodies. Cells were grown to third passage, were positive for pan-CK, p63 and Ki-67, and few cells had vimentin positive expression. As for the explants, the epidermal laminae were not stained for vimentin or Ki-67. However, some cells presented positive pan-CK and p63 expression. This study demonstrated the viability of lamellar explants of equine hooves as a form of isolating keratinocytes in primary cultures, as well as characterized the proliferation ability of such keratinocytes in monolayers.